2016
DOI: 10.1021/acs.jpcc.6b05197
|View full text |Cite
|
Sign up to set email alerts
|

Packing and Disorder in Substituted Fullerenes

Abstract: Fullerenes are ubiquitous as electron-acceptor and electron-transport materials in organic solar cells. Recent synthetic strategies to improve the solubility and electronic characteristics of these molecules have translated into a tremendous increase in the variety of derivatives employed in these applications. Here, we use molecular dynamics (MD) simulations to examine the impact of going from mono-adducts to bis-and tris-adducts on the structural, cohesive, and packing characteristics of [6,6]-phenyl-C 60 -b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 59 publications
0
32
0
1
Order By: Relevance
“…These include high-performance liquid chromatography (HPLC), 2 optical absorption, [32][33][34] uorescence spectroscopy, 32,33 static/dynamic light scattering at l > 700 nm, 18,19,22,32,33 positron lifetime spectroscopy, 20,27 electron microscopy, 22,32 small-angle neutron scattering (SANS), 14,15,[44][45][46] small-angle X-ray scattering (SAXS) 22,45,46 and theoretical calculations (molecular dynamics simulations, ab initio DFT, and others). [23][24][25][26]35,[47][48][49] Despite all these studies, the reports on the solubility and agglomeration of PC 71 BM and its comparison with PC 61 BM are still scarce 2,3 and there is in some cases a large discrepancy amongst the solubility values reported by different authors, as shown in Table 1. The most detailed comparison between the solubilities of both fullerene derivatives was performed by Kronholm et al 2 who published solubility values, determined by HPLC analysis of the liquid phase at room temperature, for PC 61 BM and PC 71 BM in different organic solvents, including chlorobenzene, toluene and chloroform.…”
Section: Introductionmentioning
confidence: 99%
“…These include high-performance liquid chromatography (HPLC), 2 optical absorption, [32][33][34] uorescence spectroscopy, 32,33 static/dynamic light scattering at l > 700 nm, 18,19,22,32,33 positron lifetime spectroscopy, 20,27 electron microscopy, 22,32 small-angle neutron scattering (SANS), 14,15,[44][45][46] small-angle X-ray scattering (SAXS) 22,45,46 and theoretical calculations (molecular dynamics simulations, ab initio DFT, and others). [23][24][25][26]35,[47][48][49] Despite all these studies, the reports on the solubility and agglomeration of PC 71 BM and its comparison with PC 61 BM are still scarce 2,3 and there is in some cases a large discrepancy amongst the solubility values reported by different authors, as shown in Table 1. The most detailed comparison between the solubilities of both fullerene derivatives was performed by Kronholm et al 2 who published solubility values, determined by HPLC analysis of the liquid phase at room temperature, for PC 61 BM and PC 71 BM in different organic solvents, including chlorobenzene, toluene and chloroform.…”
Section: Introductionmentioning
confidence: 99%
“…[15] In view of the high-cost synthesis and purification for fullerene derivatives, pristine fullerenes (e.g., C 60 and C 70 ) as interlayer materials have the advantage of being applied in commercial PSCs. [18] Rather than PC 61 BM, moreover, a pristine C 60 fullerene modification layer possesses better resistance to the PbI 2 solution. [18] Rather than PC 61 BM, moreover, a pristine C 60 fullerene modification layer possesses better resistance to the PbI 2 solution.…”
mentioning
confidence: 99%
“…[16] In addition, pristine C 60 fullerene exhibits higher electron mobility than its derivatives (e.g., [6,6]-phenyl-C61 butyric acid methyl ester that is abbreviated as PC 61 BM), [17] owing to denser package, which facilitates intermolecular charge transport. [18] Rather than PC 61 BM, moreover, a pristine C 60 fullerene modification layer possesses better resistance to the PbI 2 solution. [19] Because I − ions were observed as the main migration species in contrast to CH 3 NH 3 + (MA + ) ions for organic-halide perovskite, [20] charge transfer from I − ions to C 60 molecules benefits I − immobilization to suppress current hysteresis and light-soaking instability.…”
mentioning
confidence: 99%
“…in amorphous films are of critical importance for the formation of mesoscopic conductive networks across the bulk volume. [27,32,[45][46][47] However, accurately probing them at atomistic level still remains experimentally difficult to date. [48] Here, MD simulations were used to generate molecular packing morphologies of ITIC and its derivatives ( Figure S2, Supporting Information).…”
mentioning
confidence: 99%